Perancangan Website untuk Penerima Bantuan Langsung Tunai (BLT) di Kantor Keuchik Gampong Ceurih, Kecamatan Ulee Kareng, Kota Banda Aceh - Baridi, Muhammad; Sofyan; Salam, Abdus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to design and implement a web-based information system for managing data of Bantuan Langsung Tunai (BLT) recipients at the Kantor Geuchik Gampong Ceurih, Ulee Kareng District, Banda Aceh. The system is designed to replace the manual process, which is prone to errors such as incomplete data entry and difficulties in data retrieval. The method used in the system design is Waterfall, combined with programming languages such as HTML, PHP, CSS, and JavaScript. The system includes several forms, including login, main menu, and BLT recipient data input forms. In addition, the system generates comprehensive reports on BLT recipients, including reports based on criteria, recipient schedules, and personal data. System testing shows that the application is effective in improving efficiency, accuracy, and speed in managing BLT data. With this system, data entry and reporting processes can be carried out faster and more organized, thus facilitating operators in performing their tasks.